2022
DOI: 10.3390/jcm11051423
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends (2012–2020), Sex Differences and Predictors for Influenza Vaccination Uptake among Individuals with Chronic Obstructive Pulmonary Disease in Spain

Abstract: (1) Background: To analyze time trends, sex differences, and factors associated with influenza vaccination uptake among individuals with COPD in Spain, 2012–2020. (2) Methods: A cross-sectional study based on data from the European Health Surveys for Spain, 2020 (EHSS2020) and 2014 and from the Spanish National Health Interview Surveys for 2017 and 2012. (3) Results: The study included 65,447 participants. Prevalence of COPD was 5.9% (n = 3855). Overall, the influenza vaccination uptake among COPD patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
2
0
1
Order By: Relevance
“…[ 23 , 28 , 35 ] Current smokers had lower vaccination uptake, confirming the results of previous studies which have shown that among patients with COPD, those with unhealthy lifestyles are less likely to be vaccinated. [ 23 , 24 , 36 ] Contrary to the findings of previous studies, [ 29 , 37 ] this study showed that vaccination coverage was inversely associated with severe exacerbation history in the past year, suggesting these patients with frequent exacerbations should be a target population in which vaccination coverage need to increase. In addition, this study found that patients with low vaccination coverage had poor adherence to pharmacological and non-pharmacological therapies.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 23 , 28 , 35 ] Current smokers had lower vaccination uptake, confirming the results of previous studies which have shown that among patients with COPD, those with unhealthy lifestyles are less likely to be vaccinated. [ 23 , 24 , 36 ] Contrary to the findings of previous studies, [ 29 , 37 ] this study showed that vaccination coverage was inversely associated with severe exacerbation history in the past year, suggesting these patients with frequent exacerbations should be a target population in which vaccination coverage need to increase. In addition, this study found that patients with low vaccination coverage had poor adherence to pharmacological and non-pharmacological therapies.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction in the number of potentially fatal exacerbations also justifies effective preventive measures, including vaccination, to reduce the risk of COVID-19 infection in COPD patients and current smokers. There are gender differences in vaccine uptake in COPD patients, e.g., lower uptake of influenza vaccine among women (32) and lower uptake of COVID-19 vaccine, than men (33). This is confirmed by our present study.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in the 2014–2015 season, differences in vaccination coverage by sex of up to 13.4 percentage points were documented in Spain among men aged 80 and over compared to women in that age group [ 33 ]. Similar differences have been documented in other types of patients [ 34 , 35 , 36 ], such as splenectomized patients (with flu vaccination coverage rates of 63.3% in men and 50% in women) [ 34 ] or individuals with chronic obstructive pulmonary disease (with vaccination rates of 62.6% in men and 53.6% in women in the 2012–2013 campaign) [ 36 ]. A contributing factor to this unexpected finding is perhaps the pandemic of the new SARS-CoV-2, in which influenza vaccination to avoid possible coinfection with the two viruses may have been a particularly important reason for women to be vaccinated.…”
Section: Discussionsupporting
confidence: 73%